Edible Molluscs, Crustaceans and Holothurians from North and South Bais Bays, Negros Oriental, Philippines - Alcala, Angel C.; Alcazar, Sally (Silliman Journal, 2024)
The standing stock, distribution and harvest of the common molluscan, crustacean and holothurian species occurring in North and South Bais Bays, southern Negros, Philippines were studied for 12 months from January through December 1982. Twenty-seven species of pelecypods and gastropods, several species of crustaceans in the families Gecarcinidae, Penaeidae, Porfunidae and Grapsidae, and 16 species of holothurians were found to be harvested for food. Standing stock of pelecypods and gastropods in an area of approximately 267 ha was estimated to be about 33.5 tons (wet weight), exclusive of the mussel Modiolus metcalfei and the sea hare Dolabella auricularia. Dolabella had a standing stock of about 217 kg (wet weight) per ha in favorable areas of the bays. Standing stocks of crustaceans are unknown except for that of Cardisoma carnifex, estimated at 3300 adults and subadul per ha. Standing stock of five major species of holothurians was about 2.6 tons wet weight) per ha in favorable habitais: Annual harvest in 1982 of molluscs, crabs, shrimps, holothurians and sea hare egg masses was estimated et about 16 tons; with a market value of P77,000. Although 26 species of algae occurred in the Bays, the basis for animal production was most likely the mangrove forest and seagrass bed.